STUDENTS' MOTIVATION TO LEARN DURING THE PANDEMIC IN THE LEARNING PROCESS FROM HOME - Andriyatih, Andriyatih (Publikasi dan UKI Press UKI Toraja., 2023)
This study examines students' learning motivation during the pandemic in the learning process from home. In the learning process, motivation is needed. Motivation can arise from intrinsic (within the individual) or extrinsic (outside the individual). These two factors are very important and continuous in increasing student motivation. During the COVID-19 pandemic, the learning process is carried out from home, so learning motivation can be influenced by several factors. From the research results obtained, there are many factors that do not support the student learning process during the pandemic. These factors, among others; technological skills, internet network connections, learning media used, student capacity for online learning, and so on. Thus, it can be neglected that student motivation during the pandemic in the learning process from home has decreased.